Aggressive Pituitary Macroadenoma Treated With Capecitabine and Temozolomide Chemotherapy Combination in a Patient With Nelson’s Syndrome: A Case Report - Mirallas, Oriol; Filippi-Arriaga, Francesca; Hernandez Hernandez, Irene; Aubanell, Anton; Chaachou, Anas; Garcia-Alvarez, Alejandro; Hernando, Jorge; Martínez-Saez, Elena; Biagetti, Betina; Capdevila, Jaume (Frontiers in Endocrinology, 2021)
Nelson’s syndrome is considered a severe side effect that can occur after a total bilateral adrenalectomy in patients with Cushing Disease. It usually presents with clinical manifestations of an enlarging pituitary tumor including visual and cranial nerve alterations, and if not treated, can cause death through local brain compression or invasion. First therapeutic option is surgery but in extreme cases of inaccessible or resistant aggressive pituitary tumors; the off-label use of chemotherapy with capecitabine and temozolomide can be considered. However, the use of this treatment is controversial due to adverse events, lack of complete response and inability to predict results. We present the case of a 48-year-old man diagnosed with Nelson Syndrome with prolonged partial response and significant clinical benefit to treatment with capecitabine and temozolomide.